'Can thought go on without a body?' On the relationship between machines and organisms in media philosophy†. Issue 4 (3rd July 2016) - Balke, Friedrich
ABSTRACT: All philosophy of media has its origin in the Cartesian distinction between res cogitans and res extensa – a distinction that poses the question of whether thinking is detachable from its bodily carrier and presents the possibility of outsourcing cognitive operations to apparatuses or machines. In the Cartesian elimination of the body, Jean-Francois Lyotard identified the philosophical force of current technoscientific culture, which is in the process of freeing thinking from its forced coupling with the human body. The speculative tabula rasa brought about by the Cartesian 'demolition' takes the form of a technological wager in the twentieth century. Technology is an attempt to respond to the extreme challenge that cosmic development poses for human beings: to guarantee that thought remains possible even after the ultimate catastrophe of a solar explosion, which threatens all planetary life a few billion years from now. The technological utopia of an ultra-stable infrastructure that would enable the continuation of thought even after the demise of its hitherto ecological conditions perpetuates, on the one hand, the politico-theological notion of a second body, one equipped with mysterious forces that guarantee invincibility. On the other hand, the naturalism and the rhetoric of crisis with regard to the history of mankind at stake in this utopia of human self-assertion ignore the complex interplay of thought and the body, whose parallel relationship Spinoza first pointed out against Descartes' dualism. Rather than confine thought to the body, as in a vessel, Spinoza demonstrates that thought exists only because it is, in a certain way, affected and disposed by the body, in a physical as well as cultural sense (i.e. through objects, signs, institutions, and apparatuses).